SIFAT PAPAN PARTIKEL DARI CAMPURAN KAYU JABON DAN BAMBU ANDONG - Deazy Rachmi Trisatya; Ignasia Maria Sulastiningsih (Jurnal Penelitian Hasil Hutan, 2019)
Wastes generated from processing of jabon wood (Antochephalus cadamba Miq.) and andong bamboo (Gigantochloa pseudoarundinacea (Steudel) Widjaja) were used as raw material for particleboard manufacture. The aim of this research was to investigate the effect of particle weight ratio of jabon wood and andong bamboo on physical and mechanical properties of particleboard. Laboratory scale particleboards with the dimension of 35cm x 35cm x 1.2 cm were fabricated using liquid phenol formaldehyde adhesive with six different compositions of particle weight ratio of jabon wood and andong bamboo (100:0, 70:30, 60:40, 50:50, 40:60, and 30:70). Results showed that the physical and mechanical properties of these particleboards were significantly affected by particle weight ratio compositions. Thickness swelling of jabon wood particleboard decreased by 11.19−40% resulted from the addition of andong bamboo particles in particleboard manufacture. The addition of 40% andong bamboo particles improved the MOR value of jabon wood particleboard by 11.49%. All particleboards studied meet the Indonesian and Japanese Standard requirements of particleboard except MOE value.